1993
DOI: 10.1111/j.1741-2358.1993.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Root caries incidence and associated risk factors in middle‐aged and older adults

Abstract: Data from population-based longitudinal studies required to assess the incidence of root caries and associated risk factors are sparse in the literature. To this end, a group of 130 middle-aged and older adults were examined for root caries at baseline and at a follow-up visit between nine and 24 months (median: 16 months). Dental examinations were conducted by one examiner at a Tufts dental clinic using NIDR defined diagnostic criteria. Fifty percent of subjects in this study population developed one or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 22 publications
7
34
2
4
Order By: Relevance
“…Some factors have been identified, for example medical problems (8), reduced saliva secretion rate, which is often the side effect to medication (27,28). Steele et al (29) mention frequent sugar intake, poor hygiene, and partial dentures as factors associated with large increases in risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors have been identified, for example medical problems (8), reduced saliva secretion rate, which is often the side effect to medication (27,28). Steele et al (29) mention frequent sugar intake, poor hygiene, and partial dentures as factors associated with large increases in risk.…”
Section: Discussionmentioning
confidence: 99%
“…Those aged 75-85 years are particularly vulnerable to the disease, with the worldwide prevalence for the dentate elderly ranging from 35%-75%, and a caries attack rate ranging from 0.31/100 to 6.3/100 surfaces/year [5]. In longitudinal studies, the caries experience of the elderly people over time exceeded that reported from cohort studies of adolescents, indicating that older adult caries is as serious a problem as childhood caries [6][7][8].…”
Section: Introductionmentioning
confidence: 63%
“…Caries is especially exaggerated in high-risk minority and uninsured populations with low incomes and poor access to dental care [8]. In this examination of medication classes and caries, the investigators attempted to control for some these factors by using a large sample size from community with fluoridated water and limited the age range to 40-80 year old.…”
Section: Introductionmentioning
confidence: 99%
“…3 Günümüze kadar araştırmacılar birçok çevresel faktörü tek başına veya birlikte ele alarak çürük riskini değerlendirmişlerdir. [4][5][6][7][8][9][10][11] Bunun yanında sadece çevresel faktörlerin değerlendirilmesinin diş çürüğünün oluşumunu açıklamadığının altı çizilmiştir. Çünkü aynı çevresel risk faktörlerine maruz kalan bireylerin çürük riskinin aynı olmadığı belirlenmiş ve bu sonuç çürüğün etiyolojisinde genetik faktörlerin de rol oynadığını akla getirmiştir.…”
Section: Introductionunclassified